2019
DOI: 10.5336/nurses.2018-60409
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Factors Affecting the Standing Conditions of Patients After Surgery

Abstract: Kolesistektomi ameliyatı sonrası hastaların ayağa kalkma durumlarını etkileyen faktörlerin incelenmesidir. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Tanımlayıcı ve kesitsel tipte olan bu çalışma, bir devlet hastanesinin genel cerrahi kliniğinde yatan açık veya laparoskopik yöntemle kolesistektomi ameliyatı olan 206 hasta ile gerçekleştirilmiştir. Örnekleme dâhil edilen hastalara, araştırmacılar tarafından literatür doğrultusunda oluşturulan "Hasta tanıtım formu" ve 38 sorudan oluşan "Ameliyat sonra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Arı and Yılmaz (26), reported that the mean of post-operative time to ambulation of the patients was 7.1±3.1 hours in their study. In the study by Mahmudova and Candan Dönmez (21), it was reported that the time to ambulation of the patients after surgery was (8,27,28). It is even reported that ambulation is the most unmet and missed nursing care practice, with a rate of 84% (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arı and Yılmaz (26), reported that the mean of post-operative time to ambulation of the patients was 7.1±3.1 hours in their study. In the study by Mahmudova and Candan Dönmez (21), it was reported that the time to ambulation of the patients after surgery was (8,27,28). It is even reported that ambulation is the most unmet and missed nursing care practice, with a rate of 84% (27).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive Form: This form was prepared by the researchers with reference to the relevant literature. It consists of 17 questions about the sociodemographic characteristics and medical history of the patients [age, gender, marital status, educational status, profession, medical diagnosis, presence of chronic disease, body mass index (BMI), smoking status, previous hospitalization history, previous surgical intervention, the type of current surgical intervention, duration of anaesthesia, ASA score, duration of hospitalization, postoperative ambulation pattern and time] (9,10,21).…”
Section: Data Collection Toolsmentioning
confidence: 99%